Catalytic, Photocatalytic and Electrocatalytic Processes for the Valorisation of CO2 - Rossetti, Ilenia (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Increasing attention is being paid to the development of effective technologies for the sequestration of CO2 and its storage. Hopefully, this will result in processes that can lead to its valorisation as a chemical, e.g., for the regeneration of fuels, but also for the production of intermediates. These are usually energy demands and rather slow processes, requiring energy input and catalysts. Some examples are the innovative strategies for the hydrogenation, photoconversion, or electroreduction of carbon dioxide. This book collects original research papers, reviews, and commentaries focused on the challenges related to the valorisation and conversion of CO2.